Properties and utilization of young-age yemane (Gmelina arborea Roxb.) for lumber production - Alipon, Marina A.; Bondad, Elvina O.; Alcachupas, Pablito L.; Cortiguerra, Emelyne C. (2019)
This paper presents the lumber recovery and lumber grade yields; strength properties, namely modulus of rupture, stress at proportional limit, and modulus of elasticity in static bending; compression parallel and perpendicular-to-grain; shear; hardness; and toughness, including the cost-benefits, of 4-, 6- and 8-year old yemane (Gmelina arborea Roxb.) for lumber production. The study was conducted to evaluate the effects of age and sites on these properties, recommend its end-uses, and evaluate the cost-benefits of converting the species at different ages for lumber production. The experimental materials consisted of three trees each from three sites in Caraga Region, Philippines, namely: Pating-ay, Prosperidad, Agusan del Sur (Site 1); Nong-nong, Butuan City (Site 2); and Las Nieves, Agusan del Norte (Site 3). Standard procedures for testing the abovementioned properties were followed. In the absence of lumber grading rules for industrial tree plantation species, individual boards were graded in green condition based on the U.S. National Hardwood Lumber Association standards. On the average, the 8-year old trees obtained the highest average percent lumber recovery with 55.78%, 56%, and 54.89% for Site 1, Site 2, and Site 3, respectively. The trend of lumber recovery among sites also held true, with the 4- and 6-year old trees with values of 52% and 53.67% for Site 1, 51% and 53.33% for Site 2, and 51% and 52.11% for Site 3. Generally, the mechanical properties of 4-, 6-, and 8-year olds fell under moderately low (Class IV). All indicators show the viability of processing yemane from different diameters, ranging from 16.29 cm to 20.64 cm, belonging under 6- and 8-year-olds.
Keywords: Timber; Lumber